Analisis Dan Perancangan Sistem Pendukung Keputusan Pemberian Kredit Menggunakan Metode SAW Pada PT. BPR Artha Prima Persada - S, Elly Gustiyani; Assegaff, Setiawan (Jurnal Manajemen Sistem Informasi, 2021)
An increase in bad credit occurred at PT. BPR. Artha Prima Persada from year to year produces the performance quality of the company. For that, it takes a system that can support the decisions taken. The decision support system provides facilities to be analyzed so that the decision-making process made by entrepreneurs can be more qualified. This research uses the SAW method and Unified Modeling Language (UML) modeling tools with diagrams using Case diagrams, class diagrams, activity diagrams, and this research generates prototypes that can be implemented further so as to produce a decision support system that can be implemented at PT. BPR Artha Prima Persada.